2011
DOI: 10.1002/cbf.1725
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits invasion, migration and signalling molecules involved in cell survival and proliferation of prostate cancer cell line (PC‐3)

Abstract: Urokinase-type plasminogen activator (uPA) is a serine protease that is involved in cancer progression, especially invasion and metastasis including prostate cancer. uPA activation is mediated by transactivation of uPAR and epidermal growth factor receptor (EGF-R) in prostate cancer progression. Prostate cancer (PC-3) cells have highly invasive capacity and they express uPA and uPAR gene. PC-3 cells are treated with quercetin, which inhibits invasion and migration of PC-3 cells. Quercetin downregulates uPA, uP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…In MDA-MB-231 cells, quercetin inhibits invasion and the levels of MMP-3 [161]. In prostate cancer, treatment of PC-3 cells with quercetin decreased the expression of MMP-2/MMP-9 and inhibited invasion and migration, and the mRNA expression of uPA, uPAR, EGF, and EGFR were also downregulated [162,163]. In medulloblastoma, both the Met-induced cell migration and HGF-mediated Akt activation in a medulloblastoma cell line, DAOY, were strongly diminished by quercertin treatment [164].…”
Section: Quercetinmentioning
confidence: 95%
“…In MDA-MB-231 cells, quercetin inhibits invasion and the levels of MMP-3 [161]. In prostate cancer, treatment of PC-3 cells with quercetin decreased the expression of MMP-2/MMP-9 and inhibited invasion and migration, and the mRNA expression of uPA, uPAR, EGF, and EGFR were also downregulated [162,163]. In medulloblastoma, both the Met-induced cell migration and HGF-mediated Akt activation in a medulloblastoma cell line, DAOY, were strongly diminished by quercertin treatment [164].…”
Section: Quercetinmentioning
confidence: 95%
“…In MDA-MB-231 cells the anti-invasive effect was mediated by inhibiting MMP-3 activity [208]. In PC-3 prostate cancer cells, quercetin (50 and 100 μM for 24 h) decreased MMP-2/MMP-9 expression [209] and downregulated the mRNA of uPA, uPA receptor (uPA-R), EGF, and EGF receptor (EGF-R), thereby inhibiting invasion and migration [210]. In human glioblastoma U87 cells, quercetin blocked PMA-induced migration and invasion by inhibiting ERK-dependent COX-2 activation and MMP-9 activity [211], while in the DAOY medulloblastoma cell line, it reduced both Met-induced cell migration and HGF-mediated Akt activation [212].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Many studies have reported inhibition of proliferation and induction of apoptosis in response to various anti-cancer reagents like NO-aspirin [42,43], quercetin [44][45][46], curcumin [47][48][49], and resveratrol [50,51]. Here, we report that compounds 1-3 induced colon cancer cell death via an anti-proliferative/proapoptotic mechanism.…”
Section: Uptake Of Compounds 1-3 Was Detected Via Flow Cytometrymentioning
confidence: 60%